Characteristics of Mismatch Repair–Deficient Colon Cancer in Relation to Mismatch Repair Protein Loss, Hypermethylation Silencing, and Constitutional and Biallelic Somatic Mismatch Repair Gene Pathogenic Variants. Issue 4 (20th June 2022) - Keshinro, Ajaratu; Ganesh, Karuna; Vanderbilt, Chad; Firat, Canan; Kim, Jin K.; Chen, Chin-Tung; Yaeger, Rona; Segal, Neil H.; Gonen, Mithat; Shia, Jinru; Stadler, Zsofia K.; Weiser, Martin R.
Abstract : BACKGROUND: Mismatch repair–deficient colon cancer is heterogeneous. Differentiating inherited constitutional variants from somatic genetic alterations and gene silencing is important for surveillance and genetic counseling. OBJECTIVE: This study aimed to determine the extent to which the underlying mechanism of loss of mismatch repair influences molecular and clinicopathologic features of microsatellite instability-high colon cancer. DESIGN: This is a retrospective analysis. SETTINGS: This study was conducted at a comprehensive cancer center. PATIENTS: Patients with microsatellite instability-high colon cancer of stage I, II, or III were included. INTERVENTION: Patients underwent a curative surgical resection. MAIN OUTCOME MEASURES: The main outcome measures were hypermethylation of the MLH1 promoter, biallelic inactivation, constitutional pathogenic variants, and loss of specific mismatch repair proteins. RESULTS: Of the 157 identified tumors with complete genetic analysis, 66% had hypermethylation of the MLH1 promoter, 18% had constitutional pathogenic variants, (Lynch syndrome), 11% had biallelic somatic mismatch repair gene pathogenic variants, and 6% had unexplained high microsatellite instability. The distribution of mismatch repair loss was as follows: MLH1 and PMS2 co-loss, 79% of the tumors; MSH2 and MSH6 co-loss, 10%; MSH6 alone, 3%; PMS2 alone, 2%; other combinations, 2%; no loss, 2%. Tumor mutational burden was lowest in MLH1- and PMS2-deficient tumors. MSH6-deficient tumors had the lowest levels of tumor-infiltrating lymphocytes, lowest MSI scores, and fewest frameshift deletions. Patients with MLH1 promoter hypermethylation were significantly more likely to be older and female and to have right-sided colon lesions than patients with biallelic inactivation. Mutation was the most prevalent second hit in tumors with biallelic inactivation and tumors of patients with Lynch syndrome. LIMITATIONS: This study was limited by potential selection or referral bias, missing data for some patients, and relatively small sizes of some subgroups. CONCLUSIONS: Clinical characteristics of mismatch repair–deficient colon cancer vary with the etiology of microsatellite instability, and its molecular characteristics vary with the affected mismatch repair protein. See Video Abstract at http://links.lww.com/DCR/B984 . CARACTERÍSTICAS DEL CÁNCER DE COLON CON DEFICIENCIA EN LA REPARACIÓN DE ERRORES DE EMPAREJAMIENTO EN RELACIÓN CON LA PÉRDIDA DE PROTEÍNAS MMR, SILENCIAMIENTO DE LA HIPERMETILACIÓN Y LAS VARIANTES PATÓGENAS SOMÁTICAS DE GENES MMR CONSTITUCIONAL Y BIALÉLICO: ANTECEDENTES: El cáncer de colon deficiente en la reparación de errores de emparejamiento es heterogéneo. La diferenciación de las variantes constitucionales heredadas de las alteraciones genéticas somáticas y el silenciamiento de genes es importante para la vigilancia y el asesoramiento genético. OBJETIVO: Determinar hasta qué punto el mecanismo subyacente de pérdida de reparación de desajustes influye en las características moleculares y clinicopatológicas del cáncer de colon con alta inestabilidad de microsatélites. DISEÑO: Análisis retrospectivo. ESCENARIO: Centro integral de cáncer. PACIENTES: Pacientes con cáncer de colon con inestabilidad de microsatélites alta en estadio I, II, o III. INTERVENCIÓN: Resección quirúrgica con intención curativa. PRINCIPALES RESULTADOS Y MEDIDAS: Hipermetilación del promotor MLH1, inactivación bialélica, variante patógena constitucional y pérdida de proteínas específicas reparadoras de desajustes. RESULTADOS: De los 157 tumores identificados con un análisis genético completo, el 66 % tenía hipermetilación del promotor MLH1, el 18 % tenía una variante patogénica constitucional (síndrome de Lynch), el 11 % tenía variantes patogénicas somáticas bialélicas de algún gen MMR y el 6 % tenía una alta inestabilidad de microsatélites sin explicación. La distribución de la pérdida según la proteína de reparación del desajuste fue la siguiente: pérdida conjunta de MLH1 y PMS2, 79 % de los tumores; co-pérdida de MSH2 y MSH6, 10%; MSH6 solo, 3%; PMS2 solo, 2%; otras combinaciones, 2%; sin pérdida, 2%. La carga mutacional del tumor fue más baja en los tumores deficientes en MLH1 y PMS2. Los tumores con deficiencia de MSH6 tenían los niveles más bajos de linfocitos infiltrantes de tumores, las puntuaciones más bajas del sensor de IMS y la menor cantidad de deleciones por cambio de marco. Los pacientes con hipermetilación del promotor MLH1 tenían significativamente más probabilidades de ser mayores y mujeres y de tener lesiones en el colon derecho que los pacientes con inactivación bialélica. La mutación fue el segundo golpe más frecuente en tumores con inactivación bialélica y tumores de pacientes con síndrome de Lynch. LIMITACIONES: Sesgo potencial de selección o referencia, datos faltantes para algunos pacientes y tamaños relativamente pequeños de algunos subgrupos. CONCLUSIONES: Las características clínicas del cáncer de colon deficiente en reparación de desajustes varían con la etiología de la inestabilidad de microsatélites, y sus características moleculares varían con la proteína de reparación de desajustes afectada. Vea Resumen de video en http://links.lww.com/DCR/B984 . (Traducción—Dr. Felipe Bellolio )